(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
An assessment for Portugal continental coast of the Levelized Cost of Energy (LCOE) of a floating Wave Energy Converter (WEC) called UGEN is presented in this article. The UGEN device is composed by two well-known components: an asymmetric floater and the Wells turbine, which is activated by the reversible air flow driven by the U-shaped Oscillating Water Column (OWC). The motion of the U-shaped OWC, mainly induced by the rolling of the floater, forces the air through the duct where a Wells turbine is installed to absorb the wave energy.